2017
DOI: 10.1002/mgg3.353
|View full text |Cite
|
Sign up to set email alerts
|

Newborn genetic screening for spinal muscular atrophy in the UK: The views of the general population

Abstract: BackgroundSpinal muscular atrophy (SMA) is an inherited neuromuscular disorder and a leading genetic cause of infant death worldwide. However, there is no routine screening program for SMA in the UK. Lack of treatments and the inability of screening tests to accurately predict disease severity are among the key reasons implementation of screening has faltered in the UK. With the recent release of the first therapy for SMA (Nusinersen), calls are being made for a reconsideration of this stance; however, very li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Since a number of SMN-dependent and SMNindependent therapies are available [11], the timing of treatment is crucial for a good outcome [12,13] and available data show that presymptomatic treatment is superior to treatment after onset of symptoms [14] experts agree that newborn screening should be established [15,[16][17][18][19][20][21][22][23]. Currently first pilot projects for a genetic NBS in SMA are underway [18,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Since a number of SMN-dependent and SMNindependent therapies are available [11], the timing of treatment is crucial for a good outcome [12,13] and available data show that presymptomatic treatment is superior to treatment after onset of symptoms [14] experts agree that newborn screening should be established [15,[16][17][18][19][20][21][22][23]. Currently first pilot projects for a genetic NBS in SMA are underway [18,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…These findings can also be extrapolated to the opinion of the general public. In the United Kingdom, a survey study revealed that 84% of participants from the general public were in favor of NBS for SMA, compared to 70% support among SMA families (25). In the meantime, treatment for SMA became available and in July 2019, the Health Council of the Netherlands deemed SMA to be a suitable candidate to be included in the Dutch NBS program (26).…”
Section: Discussionmentioning
confidence: 99%
“…Most parents opted for a screening. In a former study it has been shown that there is a wide acceptance of SMA NBS in the British population 24 . Adding a genetic screening to the NBS had no negative effect on the overall acceptance of NBS.…”
Section: Discussionmentioning
confidence: 99%